SHALE CHARACTERIZATION OF THE LOWER BAONG FORMATION AS APOTENTIAL RESERVOIR IN A SHALE HYDROCARBON SYSTEM IN LANGKAT â ARU, NORTH SUMATRA - Suwanda Djohor, Denny
The uncertainty of exploration in finding large conventional hydrocarbon reserves in the North Sumatra Basin has urged an exploration study of unconventional hydrocarbon. The effort was carried out as an alternative way to find new resources by evaluating the presence of hydrocarbons directly in the source rock. United Stated is the example of the most succesful country in the world in developing non- convensional hydrocarbon in the recent decade. However, the evaluation shale gas potential in Indonesian sedimentary basin is not appropriate by using the analogy of shale characteristics in United State. Each sedimentary basin has a unique characteristics, and therefore this will effect the type of shale as well as the their mechanical rock properties. This research dissertation is limited to the analyses and syntheses of petrology that was integrated with the mechanical rock properties, based on field data and subsurface data in the Langkat-Aru area, North Sumatra. The research objective is to study the lithofacies characteristics of the Lower Baong Formation, using petrological methods (including mineralogy, texture, and microstructure), and then was integrated with the characteristics of rock mechanics; in order to determine the potential zones of reservoirs in non-conventional hydrocarbon systems. The stages of the research are divided into four stages, namely: data collection, data processing, data analyses, and syntheses. Methods employed in this study consist of outcrop observation from four transects with total length of 20.5 km and analyses of 55 rock samples in the laboratory. Laboratory works included analyses of petrographics (37 samples), calcimetry (36 samples), granulometry (36 samples), XRD (17 samples), SEM (17 samples), foraminifera (16 samples) and nannoplankton (19 samples), index properties (8 samples), uniaxial compressive strength (11 samples) and ultrasonic waves (8 samples), and also Schmidt Hammer test in the field (in 8 outcrop locations). In addition, subsurface data was also used, and in this study there are 26 wells that belongs to the working area Pertamina EP - Sumbagut Region, but only 12 wells having complete data for analysis. The results of outcrop observation and laboratory analyses (calcimetry, granulometry, XRD, and SEM) can be explained as the following. The lithofacies of the Lower Baong Formation, based on the dominant lithology and the characteristics (texture, composition, and structure), as well as CaCO3 content, can be categorized into 10 lithofacies: Calcareous Mud-shale, Calcareous Claystone, Sandy mudstone, Calcareous Mudstone, Claystone, Calcareous Silty claystone, Calcareous Clay-shale, Mudstone, Calcareous Sandy mudstone, and Mud-shale. From the results of the physical properties analyses (brittleness index, index properties, uniaxial compressive strength, ultrasonic waves, and Schmidt Hammer tests), the 10 lithofacies of Lower Baong Formation are found to have different mechanical rock characteristics. 10 lithofacies of The Lower Baong Formation, there are only 2 lithofacies that have the potential to act as reservoirs in the shale hydrocarbon system, they are as follows; a. The Calcareous Mud-shale with the criteria: porosity (2.69%), water saturation (7.35%), clay mineral content (26%-38%), brittleness index (BI = 0.51- 0.57), brittle due to the low Poisson’s ratio, and high Young’s modulus, shale thickness (> 50 meters) and marine depositional environment (Lower Neritic– Bathyal). Meanwhile the litofacies Calcareous Sandy mudstone and Sandy mudstone, with the criteria: Sandy mudstone porosity (7.31%), Sandy mudstone water saturation (28.20%), clay mineral content (16% - 31%), brittleness index (BI = 0, 60 - 0.70), shale thickness (> 50 meters) and marine depositional environment (Bathyal). Subsurface data analyses conducted log and mud log data. Based on the sequence stratigraphic analysis from log and report from Pantai Pakan Timur-3 well, and also plots between GR vs RHOB, GR vs ILD, and GR vs DT, there are 5 lithofacies that can be identified: a. Calcareous Shale intercalated with Calcareous Siltstone, and Carbonate rock; b. Calcareous Siltstone intercalated with Calcareous fine Sandstone and Calcareous Shale; c. Calcareous Shale intercalated with Calcareous Siltstone; d. Calcareous Shale intercalated with Calcareous Siltstone and Carbonate rock; e. Calcareous Shale intercalated with Calcareous Siltstone. Based on the results of the calculation of the BI (Brittleness Index) from XRD data derived from sample drill cuttings in the Pantai Pakan Timur-3 (Pertamina PHE, 2012); it shows that Calcareous Siltstone intercalated with Calcareous fine Sandstone (2187–2125 meters) and Calcareous Shale intercalated with Calcareous Siltstone (2095–2035 meters) have the highes BI value (BI = 0.51–0.52); while the Calcareous Shale intercalated with Calcareous Siltstone and Carbonate rock (2281–2223 meters) has the lowest value of BI (BI = 0.24). In summary, litofasies zone of the Lower Baong Formation in the study area that has the potential as a reservoir that can be produced economically are; The Calcareous Shale intercalated with Calcareous Siltstone and Carbonate rock, at a depth of 2220 - 2300 meters, with criteria: porosity (18.6%), water saturation (47.66%), Vshale (27.16%), brittleness index (BI = 0.51).